TINDAKAN PENCEGAHAN COVID-19 OLEH MAHASISWA UNIVERSITAS UDAYANA - Astiti, Ni Putu Ita Dewi; Kardiwinata, Made Pasek (ARCHIVE OF COMMUNITY HEALTH; Vol 8 No 3 (2021): Desember 2021, 2022)
ABSTRACT The COVID-19 case continues to rise, adolescents and young adults are classified as groups with lower level of compliance in the measures preventing the spread of COVID-19. The purpose of research is to identify the association between the characteristics of sociodemographic, the history of comorbid disease in parents, and knowledge with the preventive measures of COVID-19 by udayana university students. The design of this study is an observational study with a cross-sectional study design on 80 students selected through multistage random sampling. The results showed that 61,25% of students had good COVID-19 practice. Students often visit crowded places 47,50%, do not keep a distance of 28,75%, and often touch the mouth, nose, and eye before washing their hands 30%. The simple logistic regression test showed that gender (OR=1,9), parent’s occupational status (OR=1,62), and comorbid history in parents (OR=1,68) as risk factors of COVID-19 prevention measures. Meanwhile, age, faculty, and knowledge are not risk factors for COVID-19 prevention measures. For reaseachers who are interested in this topic, expected to examine the determinants factors that influence poor COVID-19 prevention measures such as frequent public visits, often touching the mouth, nose, and eye before washing their hands. Keyword: COVID-19, Prevention, Udayana University Student